Effect of mass addition on the vibrational properties of wood and its application - Yoshitaka Kubojima (Journal of Wood Science)
Abstract A vibration test, which does not require a complex measuring technique, is a simple and nondestructive method for measuring elastic constants. The strength of wood can be estimated using a vibration test because of the positive relationship between the dynamic Young’s modulus and strength. The vibrational properties of wood are affected by inhomogeneities in the specimen (knots and holes), grain angle, dimensions of the specimen, temperature, humidity (moisture content) and end conditions. Frequency equations that consider additional mass and defects in a wood specimen were shown for various vibration modes. The effects of sections of differing quality within a wood specimen, such as knots and holes on the results of vibration tests can be discussed using the aforementioned frequency equations, the shapes of bending vibration waves generated by the tapping of wood specimens determined using a transfer function, resonance frequency shifts of a power spectrum due to defects, and the dependence of Young’s modulus on the resonance mode number. The mass and Young’s modulus of the lumber in a stack and beams of timber guardrails can be estimated without weighing.